Operation and Maintenance Expenditure Cost Recovery - Misra, Smita (World Bank, Washington, DC, 2014)
The operation and maintenance (O&M) expenditures incurred on rural water supply schemes in India is commonly much less than required and this has serious implications on their performance. This is one of the major findings of the 10-state (Punjab, Maharashtra, Kerala, West Bengal, Orissa, Tamil Nadu, Karnataka, Andhra Pradesh, Uttar Pradesh, and Uttarkand) study on the Effectiveness of Rural Water Supply Schemes undertaken by the World Bank at the request of the Government of India. The study also analyzed the issue of cost recovery, which is generally low, but differs across states, among technologies, and between demand-driven and supply-driven schemes.